Bibliometric analysis of DEMATEL method - Koca, Gözde; Yıldırım, Seda (Decision Making: Applications in Management and Engineering, 2021)
In this study, a bibliometric analysis of the studies evaluated with DEMATEL (Decision Making Experiment and Evaluation Laboratory Method), one of the MCDM methods in Web of Science, was performed according to various performance indicators. The total number of DEMATEL publications examined is 1963 documents. When DEMATEL studies are evaluated in terms of countries, it is seen that China is the leader (553 documents; 28.17%). The most cooperative country is China. The country with the highest h-index is Taiwan (62). Journal of Cleaner Production is the most efficient journal (96; 4.88%). National Chiao Tung University (102, 5.19%) is ranked as the most efficient institution in DEMATEL research. Among the most used words are "Model", "DEMATEL", "Selection", "Management", "fuzzy DEMATEL".